THE LEVEL OF KNOWLEDGE OF ECONOMICS TEACHERS INFLUENCES THEIR WILLINGNESS TO IMPLEMENT KURIKULUM TINGKAT SATUAN PENDIDIKAN - Lisa Agustina; Nor Aishah Buang; Muhammad Hussin (Jurnal Ilmu Sosial dan Humaniora, 2017)
The purpose of this study was to identify the relationship between knowledge and willingness amongst teacher of Economics in implementing kurikulum tingkat satuan pendidikan. This study used a questionnaire with 109 teachers from twelve middle schools in Aceh Besar, Indonesia, directly involved in the processes of implementing the curriculum. Descriptive analyses used were frequency, percent, mean value and standard deviation. It is found that the level of knowledge of the teachers is at a moderate level with an overall mean value of 3.04. The level of willingness also is at a moderate level with an overall mean value at 3.46. An inferential statistical correlation test was used to test hypotheses. It is found that there is a positive relationship between the level of knowledge and the level of willingness. It can be concluded that necessary knowledge will influence the willingness of the teachers to implement the curriculum.